Evaluation of sex hormones in epilepsy patients - Kurt, B.; Mutlu, Aytül; Bastan, Birgül; Balcı, Belgin Petek; Özer, Fahriye; Çokar, Özlem (Wiley-Blackwell, 2015)
[Abstract Not Available]
31st International Epilepsy Congress -- SEP 05-09, 2015 -- Istanbul, TURKEY
WOS: 000365756500134
Keywords: Sex Hormones; Epilepsy